Qualitative insights into the psychological stress before and during colposcopy: a focus group study. (4th November 2013) - Bosgraaf, Remko P.; de Jager, Willemieke C.C.; Servaes, Petra; Prins, Judith B.; Massuger, Leon F.A.G.; Bekkers, Ruud L.M.
Abstract: Objective: To determine the reasons for women's anxiety and psychological stress before and during colposcopy, in order to define strategies to decrease their stress. Methods: Qualitative study with 15 women participating in four focus groups between April 2011 and April 2012. All participants were diagnosed with a cervical cytological abnormality and attended a gynecologist's clinic to undergo colposcopy. The focus group interview was audio-taped and transcribed verbatim. The data were analyzed using qualitative content analysis to identify themes. Results: Psychological stress before colposcopy was seen as being caused by unsatisfactory explanation of abnormal cervical smears and the colposcopy procedure itself. Additionally, a fear of cancer, pain and discomfort, embarrassment, waiting time in the hospital, and a longer interval between referral and the actual colposcopy appointment increased psychological stress and anxiety. Women indicated that more detailed and practical information about the cervical smear result and the colposcopy procedure may reduce stress and anxiety. Conclusion: In order to minimize the adverse psychological consequences of an abnormal cervical smear and colposcopy, timely, practical and detailed information needs to be provided to the women, and waiting and access times need to be as short as possible. These measures may reduce the psychological stress and anxiety, however some stress and anxiety will always remain, and may even be desirable in order to ensure proper follow-up of abnormal cervical smears.